DETEKSI DINI PENINGKATAN KINERJA KARYAWAN - Desi Anjarwati; Sri Yuni Widowati; Aprih Santoso; Nir Setyo Wahdi (Unitri Press, 2021)
The purpose of this study was to analyze the impact of the work environment, leadership and motivation on the performance of the Sewing Section employees of PT Hop Lun Indonesia. This research was a survey with a total sample of 93 employees. The data was collected through the distribution of a list of questions, while the later data will be analyzed using multiple regression tests. The results show that the work environment, leadership, motivation have a significant and positive impact on employee performance with a coefficient of determination of 0.623 which means that the work environment, leadership and motivation factors have an impact on the performance of employees in the sewing section at PT Hop Lun Indonesia by 62.3% while the difference is 37.7. % can be influenced by other variables such as incentives and organizational culture.